Compensation and Discipline on Performance Through Employee Motivation in the Secretariat - Heriani Heriani; Syamsul Alam (STIE Amkop Makassar, 2020)
The research location is at the DPRD Secretariat of Soppeng Regency. The sample in this study used the census method where the entire population was sampled in the study as many as 103 employees. In conducting statistical tests using path analysis. The results showed that compensation had a positive and significant effect on employee motivation. Discipline has a positive and significant effect on employee motivation. Compensation has a positive and significant effect on performance. Discipline has a positive and significant effect on performance. Employee work motivation has a positive and significant effect on performance. Compensation has a positive and significant effect on performance through employee motivation. Discipline has a positive and significant effect on performance through employee work motivation at the Soppeng Regency DPRD Secretariat.